Experimental Investigation and Prediction of Flatness and Surface Roughness During Face Milling Operation of WCB Material. (2016) - Sheth, Saurin; George, P.M.
Abstract: In this work, effect of machining parameters spindle speed, feed and depth of cut were investigated during Face Milling of Wrought Cast Steed grade B (WCB). WCB is widely used in manufacturing valves due to its less cost. 2 3 full factorial design with four centre points is selected to perform the reliable experiments. Here the response parameters selected are surface roughness and flatness, a form control of Geometric Dimensioning & Tolerancing (GD&T). The values of flatness and surface roughness affect a lot during leakage testing of dual plate check valve. To achieve the desire value of flatness and surface roughness machining parameters need to be controlled. The right selection of process parameters can be achieved through a predictive model. ANOVA has been carried out to know the significance of input parameters. The values predicted from the model and experimental values are very close to each other.